Analisis Potensi Pemanfaatan Energi Matahari Melalui Panel Surya di Kota Medan - Anisa Niwanda; Elsa Kardiana; Muhammad Arif; Putri Rahmadani; Ridho Amalan Saufi; Suandro Mangihut Manik (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the potential and challenges of utilizing Solar Power Plants (PLTS) in Medan City, which is geographically located near the equator and receives high exposure to sunlight throughout the year. The method used is a literature review with a narrative review approach that analyzes secondary data from various journals and relevant scientific articles. The results of the study show that Medan City has an average annual horizontal global solar radiation intensity of 463.61 W/m², with the potential for electrical power that can be generated from rooftop solar panels reaching 748.57 MW (monocrystalline), 598.85 MW (polycrystalline), and 299.43 MW (thin film). This potential is comparable to the capacity of large-scale power plants. The use of PLTS contributes to reducing carbon emissions, increasing energy security, creating jobs, and developing the local economy. However, challenges such as high installation costs, limited suitability of roof structures, and low public awareness are still major obstacles in the implementation of this technology. Therefore, synergy is needed between government policies, public education, and technological innovation to optimize the use of solar energy in urban areas such as Medan.